School managers development paths: reference group - Nascente, Renata (Universidade Estadual Paulista, Faculdade de Ciências e Letras de Araraquara, 2017)
This article aims at presenting and discussing the development path taken by an educators group in the context of a course offered by São Paulo State Education Bureau through the Reference Groups to state public school principals, coordinators and supervisors, during two years and a half, from June 2011 until October 2013. The problem was divided into two basic questions: which were the group development process main features? Was there any sort of specific articulation between the course and the educational practices of the group? These questions were problematized based on two democratic management fundamental principles: autonomy and participation. The article is organized in three parts: in the first one, the course is characterized and the investigation methodology is presented. In the following one, which comprises three phases of the course in study, 2011, 2012 e 2013, the group development paths are discussed. In the third part we analyze and discuss the development of the educators under the light of our theoretical framework. In our final considerations we explicit our views regarding the course, focusing the possible articulations between theorizations and school practices and the development of autonomy and participation conceptions within the group.